MAKNA TEOLOGI SESAJI TRADISI RUWATAN DESA PADA MASYARAKAT JAWA DI DESA KUMENDUNG, KECAMATAN MUNCAR, KABUPATEN BANYUWANGI, JAWA TIMUR - Relin D.E.; i Gusti Ayu Kartika (UHN IGB Sugriwa Denpasar, 2022)
Ruwatan Desa offerings are a hereditary tradition in Javanese culture, especially in Kumendung Muncar Village, Banyuwangi, which is held once a year in the month of Sura (Javanese calendar) around August of the Gregorian calendar. The series of implementations begins with making donations to the needy and on the peak day, residents bring offerings in the form of tumpeng and other things to the village hall, followed by a prayer together and continued by parading the tumpeng around the village, at night doing gendurenan and wayang performances, the next morning after the puppet performance ends, it is filled with Pray together and then eat a cone with grilled chicken meat and vegetables. The event is over. This implementation is also from the theological view that as a form of petition to God in his manifestation as Lord Vishnu as the protector of the world, Dewi Sri the symbol of fertility and Hyang Bawu Rekso as the ruler of the region with the aim that the residents and the area of Kumendung Village always get harmony between humans and nature, humans and their environment, humans and humans with the environment. All these things are connected with humans and nature is a unity. In addition, as a form of gratitude for the gift of God Almighty, both in the form of where God is, God Almighty and God is most gracious, which is symbolized by abundant harvests, health and prosperity. The relationship between humans, God and nature is an element that cannot be separated from each other even though in modern times like today, nature seems to be an object to strengthen and continue human life throughout the ages. This research was conducted by literature study method. Agriculture is a very risky sector, so government support is needed